HUBUNGAN KEMAMPUAN BELAJAR MANDIRI DENGAN MOTIVASI BELAJAR JARAK JAUH SELAMA PANDEMI COVID-19 PADA MAHASISWA FAKULTAS KEDOKTERANUNIVERSITAS MUHAMMADIYAH SUMATRA UTARA - EKA RETNING OKTAVANNY; HEMMA YULFI (JURNAL ILMIAH KOHESI, 2023)
In order to overcome and decide the spread of Covid-19 that has been declared pandemic since March of 2020, the Indonesian government has issued a policy of physical distancing when being in the public. This has caused a major impact on various fields in Indonesia, especially the education sector. Physical distancing has changed the method of learning that is usually done face-to-face on campus, and must be changed to an online learning method. This drastic change is likely to affect students' learning motivation. Learning motivation is a condition that encourages students to learn. This study aims to determine the relationship between independent learning ability and distance learning motivation during the Covid-19 pandemic in students of the Medical Faculty, Universitas Muhammadiyah Sumatera Utara (UMSU). This research is an analytic study using a cross-sectional design. The number of subjects in this study was 200 people who were taken by stratified random samples. Primary data collection was done by using a questionnaire. Data were analyzed by contingency coefficient hypothesis testing using SPSS. Most of the students had good independent learning abilities (n = 106 or 53%) and high motivation (n = 86 or 43%). The results of the analysis using contingency coefficient test obtained p value of 0.001 and a correlation coefficient of 0.400. There is a moderate correlation between independent study ability and distance learning motivation during the Covid-19 pandemic among students in Medical Faculty of UMSU. Keywords: Covid-19, distance learning ability, learning motivation.